Effect of thermal/pressure processing and simulated human digestion on the immunoreactivity of extractable peanut allergens. (July 2018) - Bavaro, Simona L.; Di Stasio, Luigia; Mamone, Gianfranco; De Angelis, Elisabetta; Nocerino, Rita; Canani, Roberto Berni; Logrieco, Antonio F.; Montemurro, Nicola; Monaci, Linda
Abstract: Peanut allergy is one of the most widespread types of food allergies especially affecting developed countries. To reduce the risk of triggering allergic reactions, several technological strategies have been devised to modify or remove allergens from foods. Herein we investigated the combination of high temperature and pressure on the modulation of peanuts immunoreactivity after simulated gastro-duodenal digestion. Extractable proteins of raw and autoclaved peanuts were separated on SDS-PAGE and immunogenicity was assessed by ELISA and Western Blot analyses. Proteins surviving the heat treatment and reacting towards allergic patients' sera were analysed and attributed to Ara h 3 and Ara h 1 proteins by untargeted LC-high resolution-MS/MS. A progressive reduction in the intensity of the major allergen proteins was also highlighted in the protein fraction extracted from autoclaved peanuts, with a total disappearance of the high molecular allergens when samples were preliminary exposed to 2 h hydration although the lower molecular weight fraction was not investigated in the present work. Furthermore, raw and processed peanuts underwent simulated digestion experiments and the IgE binding was assessed by using allergic patients' sera. The persistence of an immunoreactive band was displayed around 20 kDa. In conclusion, the synergistic effects of heat and pressure played a pivotal role in the disappearance of the major peanut allergens also contributing to the significant alteration of the final immunoreactivity. In addition, the surviving of allergenic determinants in peanuts after gastrointestinal breakdown provides more insights on the fate of allergenic proteins after autoclaving treatments. Graphical abstract: Highlights: Peanuts autoclaving and hydrating produced a decrease in protein content and a reduction in immunoreactivity A difference in the final immunoreactivity was displayed with a significant loss of reactivity especially under non reducing conditions. In-vitro digestion experiments on processed peanuts confirmed the persistent immunoreactivity attributed to Ara h 3